Development of a hydro-mechanical sequencer for automation of net-sprinkler irrigation - Vanessa de Fátima Grah; Tarlei Arriel Botrel; Fernando Campos Mendonça (Acta Scientiarum: Technology, 2014)
The automation of irrigation systems has been widely implemented in Brazil in recent years, which is necessary due to operational requirements, such as irrigation of large areas at night, and subdivision of the irrigated area because of restricted use of water sources. This study developed and evaluated a hydro-mechanical device for automatic sequencing of net-sprinkler systems. The prototypes were made and evaluated at the Laboratory of Hydraulics and Irrigation, Department of Biosystems Engineering (Esalq-University of São Paulo). It was assembled a net-sprinkler irrigation with four sprinklers with a sequencer prototype installed on each of them, consisting of a volume timer and a three-way valve with a trigger system. Tests indicated that the irrigation time per sprinkler were similar to those calculated for each timer. The system has proved to be a feasible alternative for automated, sequenced operation of sprinklers in a net-sprinkler system.